Why Organization Studies Should Care More about Gender Exclusion and Inclusion in Sport Organizations - Lucy V. Piggott; Jorid Hovden; Annelies Knoppers (Emerald Publishing Limited, 2024)
Sport organizations hold substantial ideological power to showcase and reinforce dominant cultural ideas about gender. The organization and portrayal of sporting events and spaces continue to promote and reinforce a hierarchical gender binary where heroic forms of masculinity are both desired and privileged. Such publicly visible gender hierarchies contribute to the doing of gender beyond sport itself, extending to influence gender power relations within sport and non-sport organizations. Yet, there has been a relative absence of scholarship on sport organizations within the organizational sociology field. In this paper, we review findings of studies that look at how formal and informal organizational dimensions influence the doing and undoing of gender in sport organizations. Subsequently, we call for scholars to pay more attention to sport itself as a source of gendered organizational practices within both sport and non-sport organizations. We end with suggestions for research that empirically explores this linkage by focusing on innovative theoretical perspectives that could provide new insights on gender inclusion in organizations.
10.1108/S0733-558X20240000090008; 10.1108/S0733-558X20240000090008; Sociological Thinking in Contemporary Organizational Scholarship; EBP109300890